Teaching German Language to Students of Non-Linguistic Specialties - Gulshod Umarboevna Akhmedova (Genius Journals, 2023)
This article is dedicated to the problems of teaching professional foreign language communication that are being actively developed and discussed at present by psychologists, linguists and methodologists. The article presents an analysis of modern domestic and foreign studies on the issues of foreign language teaching at the initial stage. In the study, the initial stage of foreign language learning is considered in connection with the psychological, physiological, anthropological and pedagogical factors of the age group beginning to learn a foreign language.
Keywords: German language; international communication; leading position